1997
DOI: 10.1038/sj.onc.1201299
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two novel SH2 domain-containing proteins from a yeast two hybrid screen with the ABL tyrosine kinase

Abstract: To further our understanding of the molecular mechanism of Bcr ± Abl mediated transformation, a yeast two hybrid screen was used to identify proteins binding to the Abl tyrosine kinase. Two partial cDNAs encoding novel SH2 domain-containing proteins were cloned and designated Shd and She. Both have homology to Shb, a previously reported SH2 domain-containing protein.Northern blot analysis showed that She is expressed in heart, lung, brain, and skeletal muscle, while expression of Shd is restricted to the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
0
27
0
2
Order By: Relevance
“…pB42AD-mABT1, which contains the mouse ABT1 cDNA, was isolated from the Mouse Embryo MATCHMAKER LexA cDNA Library (Clontech) using the SH2 domain of SHD (48). Both strands of the mABT1 cDNA were sequenced with an ABI 377 DNA sequencer (Perkin-Elmer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pB42AD-mABT1, which contains the mouse ABT1 cDNA, was isolated from the Mouse Embryo MATCHMAKER LexA cDNA Library (Clontech) using the SH2 domain of SHD (48). Both strands of the mABT1 cDNA were sequenced with an ABI 377 DNA sequencer (Perkin-Elmer).…”
Section: Methodsmentioning
confidence: 99%
“…mABT1 was isolated during the course of yeast two-hybrid screening using the Src homology 2 (SH2) domain of SHD, a previously identified SH2 domain-containing protein (48). The analysis carried out in this study showed that mABT1 associated directly with TBP and activated transcription from an adenovirus major late (AdML) promoter in a cell-free system.…”
mentioning
confidence: 99%
“…SHB has three paralogues: SHD, SHE and SHF (Oda et al 1997, Lindholm et al 2000. They all share sequence similarity in the C-terminus and at the phosphorylation sites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SHD exhibits limited sequence similarity with SHB in the N-terminus. SHD and SHE were identified as c-Abl interacting partners (Oda et al 1997), whereas SHF was characterized based on sequence homology with SHB (Lindholm et al 2000). Whereas little is known about the functions of SHD and SHE, SHF has been reported to negatively regulate anaplastic lymphoma kinase (ALK) signaling (Takagi et al 2013) and participate in PDGFRA signaling (Lindholm et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Frequentemente está desregulado no câncer, sendo hiporegulado ou perdido em alguns tumores e superexpresso em outros (Havre et al,2008;Sulda et al, 2006). Wesley et al (1999) SHE, domínio SH2 contendo a proteína E, constitui uma proteína do domínio de SH2, cujo RNAm foi encontrado em coração, pulmão, cérebro e músculo esquelético de tecido murino (Oda et al, 1997). Como o domínio SH2 pode estar presente em diferentes moléculas de modo a exercer diversos efeitos, é difícil predizer se ocorre uma atuação oncogênica em SH2 e, consequentemente em SHE, como no oncogene Src.…”
Section: Caracterização Imunocitoquímica Das Proteinas Cd14 Dpp4 E Vunclassified